2024
DOI: 10.1215/03616878-11066304
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Perspectives on Health Equity: Results from a Nationally Representative Survey on US Public Perceptions of COVID-19 Disparities in 2023

Sarah E. Gollust,
Chloe Gansen,
Erika Franklin Fowler
et al.

Abstract: Republicans and Democrats responded in starkly different ways to the COVID-19 pandemic, from their attitudes in 2020 about whether the virus posed a threat to whether the pandemic ended in 2023. The consequences of COVID-19 for health equity has been a central concern in public health, and the concept of health equity has also been beset by partisan polarization. In this essay, we present and discuss nationally-representative survey data from 2023 on U.S. public perceptions of disparities in COVID-19 mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, in a separate analysis of elected officials and equitable health information by political partisanship, we found that Democrats were more likely than Republicans to share public information on Twitter addressing health barriers. These findings emphasize the need for what Gollust et al (2023) refer to as depolarizing public health. One potential path forward, especially on social media platforms, is what Fowler et al refer to as an "inoculation language, " where individuals receive a warning of potential controversy or political bias before reading a post (Fowler, 2022).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, in a separate analysis of elected officials and equitable health information by political partisanship, we found that Democrats were more likely than Republicans to share public information on Twitter addressing health barriers. These findings emphasize the need for what Gollust et al (2023) refer to as depolarizing public health. One potential path forward, especially on social media platforms, is what Fowler et al refer to as an "inoculation language, " where individuals receive a warning of potential controversy or political bias before reading a post (Fowler, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…However, we expect the partisanship of the elected officials in our sample to explain our dependent variable. Previous work suggests stark differences in partisanship in acknowledging health inequities (Gollust et al, 2023). During the pandemic, Democrats exhibited higher rates of risk perception in response to the pandemic (Bruine de Bruin et al, 2020) and were more likely to engage in healthy and safe behaviors during the pandemic (Gadarian et al, 2021) compared with Republicans.…”
Section: This Studymentioning
confidence: 99%